(untitled) (Malaysian Journal of Civil Engineering, 2018)
This paper presents an experimental study of the desiccation-induced volumetric shrinkage strain for two compacted soils classified as A (A-6) and B (A-7-6)according to the Association of American States Highway and Transportation Officials (AASHTO) Classification System and CL according to the Unified Soil Classification System (USCS). The samples were prepared using three compactive efforts of Reduced Proctor (RP), Standard Proctor (SP) and Modified Proctor (MP) at moulding water contents relative to optimum (i.e. -2, 0, +2 and +4%). Samples were extruded from the compaction moulds and allowed to air dry in the laboratory in order to assess the variation of desiccation-induced shrinkage on the material with days and its potentials as a hydraulic barrier in waste containment applications. Results showed that soils compacted using the higher compactive effort showed lower values of volumetric shrinkage strain (VSS) due to the closer packing of soil fabric as a result of higher energy. Similarly, VSS increased with higher moulding water content for specimens compacted on the wet side of the optimum and contain much water as against the specimens compacted on the dry side of the optimum which had less water. At 7 and 14 days cured specimens using the RP compactive effort showed similar features, and up to 2% on the dry side of the optimum for 0 and 21 days cured specimens. The SP compactive effort for 7 and 14 days cured specimens yielded the peak dry densities at 2% on the wet side of optimum and at optimum. The MP compactive effort, the samples compacted at 2% on the wet side of optimum and 2% on the dry side of optimum showed similar behaviours for the hydration periods of 0 to 14 days curing period considering soil sample A. For soil sample B, at 14 and 21 as well as 7 and 21 days cured specimens showed highest dry densities with similar features for, 2% on the wet side of optimum up to the optimum; but changes at 2% on the dry side of optimum for both RP and SP compactive efforts respectively. The predicted models measured adequately the estimation of VSS value using the analysis of variance (ANOVA) and gave good indication of validity.